Relationship Between Level of Physical Activity and Subjective Musculoskeletal Pain Among Work from Home Adults - Wong, Sai Kiong; Gaspar, Edwin; Vinodhkumar, Ramalingam (INTI International University, 2023)
Introduction: World Health Organization has defined physical activity as any physiological movement that needs energy expenditure and is produced by skeletal muscles. Due to the COVID-19 Pandemic, the government has imposed a lockdown to reduce the infection rate. Hence, many industries have moved to work from home platforms. Based on the studies, it is believed that these restrictions have caused a reduction in physical activity and an increase in sedentary behavior, which leads to musculoskeletal disorders. Objective: The purpose of this study is to determine the relationship between level of physical activity and subjective musculoskeletal pain in adults who work from home. Methodology: An online questionnaire distributed via Google Form links was sent to those who have been working from home (WFH) during and after COVID-19 in the past few years in Malaysia. The collected data was then analysed using the Pearson chi-square test using SPSS version 26 Mac OS. The Baecke Physical Activity Questionnaire and the Nordic Questionnaire were used to determine the participants' levels of physical activity and musculoskeletal pain. Result: This study found that many of the respondents experienced neck pain (n = 98, 54%), shoulder pain (n = 75, 41%), and low back pain (n = 94, 51.9%) during the past year. Further, the study findings revealed a significant relationship between neck (p = 0.014) and hip pain (p = 0.004) with the work index, wrist pain (p = 0.002) with the leisure index, and ankle joint pain (p = 0.024) with the work and sport index. Conclusion: According to the findings, WFH decrease the level of participants' physical activity, thus leading to an increase in musculoskeletal pain over the neck, shoulder, and low back.